ANALISIS PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN (Studi Kasus PDAM Kota Surakarta) - Lukman Hakim; Kusdiyanto Kusdiyanto (Benefit: Jurnal Manajemen dan Bisnis, 2011)
The research examined the impact corporate culture  toward performance of work in the PDAM Surakarta.  The objective of research was to analyze whether the variable of worker behavioral attributes model of corporate culture consisting of innovation, attention to detail, outcome orientation, people orientation, team orientation, agresivenes and stability significanly affecting the work motivation.  The sampling as many as 73 persons was taken by using case study method. They comprised the workers and managers whose different departement. From the 82 persons taken as samples through questioner sheets,  75 quistioner sheets were returned but one of  them was damaged. Therefore, there wereonly 73 quistioner sheets which were valid to be analyzed. The result of regression analysis by using the instrument called the program SPSS version 11.50 showed that attention to detail, outcome orientation, team orientation and stability have significant influence toward the followers’ performance.   Whereas the others variable  such as innovation, negative emotion, intervence, faulty attribution, disagreement have effect positively  toward the work of motivation. Whereas the behaviors such as  innovation, people orientation have no significant influence toward the  followers’ performance in PDAM Surakarta.